Crisis Based on a Play by Leck Fischer - Fischer, Leck (Tartan Video, 2004)
In Ingmar Bergman's feature directing debut, urban beauty-shop proprietress Miss Jenny arrives in an idyllic rural town one morning to whisk away her eighteen-year-old daughter, Nelly, whom she abandoned as a child, from the loving woman who has raised her. Once in Stockholm, Nelly receives a crash course in adult corruption and wrenching heartbreak. [www.criterion.com]